Transcriptional Regulation of NK Cell Development by mTOR Complexes - Yang, Chao; Malarkannan, Subramaniam (Frontiers in Cell and Developmental Biology, 2020)
The mechanistic target of Rapamycin (mTOR) is essential for multiple cellular processes. The unique roles of mTOR complex 1 (mTORC1) or mTOR2 in regulating immune functions are emerging. NK cells are the major lymphocyte subset of innate immunity, and their development and effector functions require metabolic reprogramming. Recent studies demonstrate that in NK cells, conditionally disrupting the formation of mTORC1 or mTOR complex 2 (mTORC2) alters their development significantly. Transcriptomic profiling of NK cells at the single-cell level demonstrates that mTORC1 was critical for the early developmental progression, while mTORC2 regulated the terminal maturation. In this review, we summarize the essential roles of mTOR complexes in NK development and functions.